LEGAL STRATEGIES IN HANDLING SPATIAL CONFLICT IN REGIONAL GOVERNMENT - Fadil Raid Suhariadi; Vieta Imelda Cornelis; Sri Astutik; Nur Handayati (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Spatial conflict is a common problem in regional development due to differing interests in spatial utilization. This conflict generally involves various parties, such as local governments, communities, and the private sector, who have different interests in the use of land and regional resources. This study aims to identify the factors causing spatial conflict at the local government level and analyze legal strategies that can be used to resolve such conflicts. The research method used is a normative legal approach combined with an empirical legal approach through an analysis of laws and regulations, scientific literature, and case studies of spatial conflicts in the region. The results show that spatial conflict is generally triggered by a mismatch between spatial planning and development implementation, increasing economic and investment interests, unequal public access to space, and weak coordination between government agencies. To address these problems, a comprehensive legal strategy is needed through a preventive approach in spatial planning, the implementation of dispute resolution mechanisms such as mediation, arbitration, and litigation, as well as strengthening regulations and consistent law enforcement. In addition, increasing education and socialization of spatial planning policies to the public is also an important factor in creating more transparent, participatory, and sustainable spatial governance.